Forest Management in the Interface: Reducing Fire Risk - Bruce Hull; Sarah F. Ashton; Rien M. Visser; Martha C. Monroe (EDIS, 2008)
Revised! FOR-179, a 6-page illustrated fact sheet by Bruce Hull, Sarah F. Ashton, Rien M. Visser, and Martha C. Monroe, describes qualities of fire-wise communities, structures, and landscapes in proximity with fire-dependent ecosystems, and techniques for fuel reduction. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.